网络小说的商业化和本土化：以玄幻小说《诡秘之主》为例 = The commercialization and localization of online novels: a case study of the Xuanhuan novel Lord of the Mysteries - 郭伟明 Guo, Weiming (Nanyang Technological University, 2025)
在全球化时代和互联网的普及下，网络小说迎来了快速发展的黄金时期，并逐步迈向商业化。这一过程中，网络小说不仅对社会产生深远影响，还在全球范围内掀起一股新的文化浪潮。同时，互联网的特性加速网络小说的传播与发展，使其在形式、传播方式及受众群体等方面与传统小说呈现出显著差异，既带来前所未有的机遇，也伴随着一定的挑战。值得注意的是，网络小说的 IP（Intellectual Property，知识产权） 价值丝毫不逊色于传统文学作品，如今，许多网络小说 IP 拥有极高的市场潜力和改编价值，从一个单一 IP 发展成庞大的 IP 生态，甚至最终形成涵盖影视、动漫、游戏等多元产业的“IP 乐园”。在众多网络小说类型中，玄幻题材尤为受到读者喜爱，其中，《诡秘之主》便是一个典型案例。这部作品成功地将西方克苏鲁神话与中国本土文化相结合，并且借鉴现实世界构建极具沉浸感的故事背景，使读者更容易产生共鸣。正因如此，该作品不仅受到中国读者的热烈追捧，也在海外市场获得广泛认可。此外，随着《诡秘之主》的爆火，其 IP 价值进一步拓展，被改编成动画、游戏等多种娱乐产品，展现出网络小说在文化产业中的巨大商业潜力。本文将以《诡秘之主》为例，探讨网络小说受欢迎的深层原因，并分析其在全球范围内的影响及 IP 产业链的发展趋势。In the era of globalization and widespread use of the internet, web novels have entered a period of rapid development and are becoming commercialized. In this process, web novels made a profound impact on society and sparked a new cultural wave on a global scale. Concurrently, the characteristics of the internet accelerated the dissemination and development of web novels, making them significantly different from traditional novels in terms of style, distribution, and audience. These differences bring unprecedented opportunities while also posing certain challenges. Notably, the IP value of web novels is by no means inferior to that of traditional literary works. Today, many web novel IPs hold immense market potential and adaptation value, evolving from a single IP into a vast IP ecosystem and eventually forming an "IP paradise" that spans across industries such as film, animation, and gaming. Among the various genres of web novels, Xuanhuan is particularly popular, with Lord of the Mysteries being a prime example. This work successfully integrated Western Cthulhu mythology with Chinese cultural elements while drawing inspiration from reality to construct an immersive story setting, making it easier for readers to resonate with. Hence, the novel has not only garnered immense popularity among Chinese readers but also gained widespread recognition overseas. Furthermore, following the phenomenal success of Lord of the Mysteries, its IP value has further expanded, leading to adaptations into animated shows, games, and other forms of entertainment, demonstrating the immense commercial potential of web novels in the cultural industry. This article will take Lord of the Mysteries as an example to explore the deeper reasons behind the popularity of web novels and analyze their global influence as well as the development trends of the IP industry chain.